2023
DOI: 10.1002/smll.202304958
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Activated Ultralong‐Lived Triplet Excitons of Carbon Dots for White‐Light Manipulated Anti‐Counterfeiting

Bin Xu,
Yuehan Jia,
Huiying Ning
et al.

Abstract: Room temperature phosphorescence (RTP) has emerged as an interesting but rare phenomenon with multiple potential applications in anti‐counterfeiting, optoelectronic devices, and biosensing. Nevertheless, the pursuit of ultralong lifetimes of RTP under visible light excitation presents a significant challenge. Here, new phosphorescent materials that can be excited by visible light with record‐long lifetimes are demonstrated, realized through embedding nitrogen doped carbon dots (N‐CDs) into a poly(vinyl alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…However, we found that compared with those of the corresponding CDs (3450 and 3440 cm –1 ) and CMSNa (3440 cm –1 ), the characteristic peaks of HA-CDs-CMSNa and Nap-CDs-CMSNa exhibited slight shifts in the level of O–H at 3460 cm –1 . This phenomenon indicates the formation of hydrogen bonds between the two CDs and the CMSNa matrix . Similarly, as shown in Figure S5c,d, the characteristic peaks of Nap-CDs-CMCS and HA-CDs-CMCS at 3430 cm –1 also show slight changes from those of the corresponding CDs (3440 and 3450 cm –1 ) and CMCS (3440 cm –1 ), indicating that hydrogen bonds are also formed between the two CDs and the CMCS matrix.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…However, we found that compared with those of the corresponding CDs (3450 and 3440 cm –1 ) and CMSNa (3440 cm –1 ), the characteristic peaks of HA-CDs-CMSNa and Nap-CDs-CMSNa exhibited slight shifts in the level of O–H at 3460 cm –1 . This phenomenon indicates the formation of hydrogen bonds between the two CDs and the CMSNa matrix . Similarly, as shown in Figure S5c,d, the characteristic peaks of Nap-CDs-CMCS and HA-CDs-CMCS at 3430 cm –1 also show slight changes from those of the corresponding CDs (3440 and 3450 cm –1 ) and CMCS (3440 cm –1 ), indicating that hydrogen bonds are also formed between the two CDs and the CMCS matrix.…”
Section: Resultssupporting
confidence: 61%
“…This phenomenon indicates the formation of hydrogen bonds between the two CDs and the CMSNa matrix. 44 Similarly, as shown in Figure S5c,d, the characteristic peaks of Nap-CDs-CMCS and HA-CDs-CMCS at 3430 cm −1 also show slight changes from those of the corresponding CDs (3440 and 3450 cm −1 ) and CMCS (3440 cm −1 ), indicating that hydrogen bonds are also formed between the two CDs and the CMCS matrix. In addition, compared with Nap-CDs and HA-CDs, Nap-CDs-CMCS and HA-CDs-CMCS show weak new peaks at 1030 and 1120 cm −1 , respectively, which are caused by the stretching vibration of the C−N bond, indicating that the partial carboxyl groups on the surface of CDs may react with partial amino groups in CMCS to form amide bonds, thus further connecting the CDs to CMCS chains.…”
Section: Studies Of Cd-based Rtp Compositessupporting
confidence: 60%
“…UV irradiation not only has the potential risk for human health and may be easily mimicked, but it is also inconvenient in daily life. 29 In contrast, a low-power white light source (such as a flashlight on a mobile phone) is safer for human health and has been widely used in our daily lives and is more convenient to acquire and apply. To our knowledge, only a few reports have realized visible light-excited TADF via dropping some electronegative elements (such as composite matrix to redshift the absorption bands.…”
Section: Introductionmentioning
confidence: 99%
“…could protect the triplet states via the covalent or hydrogen bonds. A series of CDs@ zeolite composite systems were proposed by Yu’s groups in recent years, and these composites exhibit various TADF emissions due to the rigid structures via the covalent bonds between matrix materials and CDs. However, most CDs-based TADF emissions have reported a need for the excitation illumination of UV light (<400 nm) due to the limitation of absorption bands. UV irradiation not only has the potential risk for human health and may be easily mimicked, but it is also inconvenient in daily life . In contrast, a low-power white light source (such as a flashlight on a mobile phone) is safer for human health and has been widely used in our daily lives and is more convenient to acquire and apply.…”
Section: Introductionmentioning
confidence: 99%
“…For assembling CD-based LEDs, one uses CDs as emitters by constructing multilayer electroluminescent devices, while the other uses photoluminescence (PL) characteristics of CDs pumped by conventional GaN-based UV or blue LED chips. [7][8][9][10][11][12][13] The former benefits to realizing large-size displays and lighting. The stateof-the-art CDs-based electroluminescent LEDs are assembled using pure CDs emitter [14][15][16][17][18] or CDs-doped guest-host emitting system.…”
Section: Introductionmentioning
confidence: 99%